The effect of strength training on IL-6 levels and muscle fitness: an empirical study on sedentary adolescents - Yanuar Alfan Triardhana; I Dewa Made Aryananda Wijaya Kusuma; Bayu Agung Pramono; Shery Iris Zalillah; Dewangga Yudhistira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The global rise in sedentary lifestyles among urban adolescents increases inflammatory markers such as interleukin-6 (IL-6) and decreases physical fitness, necessitating effective interventions.